Methane Emissions Offset Net Carbon Dioxide Uptake From an Alpine Peatland on the Eastern Qinghai‐Tibetan Plateau. Issue 19 (5th October 2021) - Peng, Haijun; Chi, Jinshu; Yao, Hu; Guo, Qian; Hong, Bing; Ding, Hanwei; Zhu, Yongxuan; Wang, Jie; Hong, Yetang
Abstract: Peatlands store large amounts of carbon (C) and actively exchange greenhouse gases (GHGs) with the atmosphere, thus significantly affecting global C cycle and climate. Large uncertainty exists in C and GHG estimates of the alpine peatlands on Qinghai‐Tibetan Plateau (QTP), as direct measurements of CO2 and CH4 fluxes are scarce in this region. In this study, we provided 32‐month CO2 and CH4 fluxes measured using the eddy covariance (EC) technique in a typical alpine peatland on the eastern QTP to estimate the net C and CO2 equivalent (CO2 ‐eq) fluxes and investigate their environmental controls. Our results showed that the mean annual CO2 and CH4 fluxes were −68 ± 8 g CO2 ‐C m −2  yr −1 and 35 ± 0.3 g CH4 ‐C m −2  yr −1, respectively. While considering the traditional and sustained global warming potentials of CH4 over the 100‐year timescale, the peatland acted as a net CO2 ‐eq source (1, 059 ± 30 and 1, 853 ± 31 g CO2 ‐eq m −2  yr −1, respectively). The net CO2 ‐eq emissions during the non‐growing seasons contributed to over 40% of the annual CO2 ‐eq budgets. We further found that net CO2 ‐eq flux was primarily influenced by global radiation and soil temperature variations. This study was the first assessment to quantify the net CO2 ‐eq flux of the alpine peatland in the QTP region using EC measurements. Our study highlights that CH4 emissions from the alpine peatlands can largely offset the net cooling effect of CO2 uptake and future climate changes such as global warming might further enhance their potential warming effect. Key Points: CH4 emissions offset the net CO2 uptake from an alpine peatland on eastern Qinghai‐Tibetan Plateau The alpine peatland showed a net radiative warming effect Global radiation and soil temperature were dominant abiotic controls of net CO2 ‐eq flux variations